Molecular and functional characaterization of the novel odorant-binding protein gene AccOBP10 from Apis cerana cerana. (28th November 2020) - Guo, Dezheng; Hao, Cuihong; Cui, Xuepei; Wang, Ying; Liu, Zhenguo; Xu, Baohua; Guo, Xingqi
Abstract: Odorant-binding proteins (OBPs) play an important role in odour perception and transport in insects. However, little is known about whether OBPs perform other functions in insects, particularly in Apis cerana cerana . Within this study, an OBP gene ( AccOBP10 ) was isolated and identified from A. c. cerana . Both homology and phylogenetic relationship analyses indicated that the amino acid sequence of AccOBP10 had a high degree of sequence identity with other members of the gene family. Analysis of quantitative real-time PCR (qRT-PCR) showed that AccOBP10 mRNA was expressed at higher levels in the venom gland than in other tissues. The mRNA transcript expression of AccOBP10 was upregulated by low temperature (4°C), hydrogen peroxide (H2 O2 ), pyridaben, methomyl and imidacloprid but downregulated by heat (42°C), ultraviolet light, vitamin C, mercuric chloride, cadmium chloride, paraquat and phoxim. Expression of AccOBP10 under abiotic stress was analysed by western blotting, and the results were consistent with those of qRT-PCR. And as a further study of AccOBP10 function, we demonstrated that knockdown of AccOBP10 by RNA interference could slightly increase the expression levels of some stress-related genes. Collectively, these results suggest that AccOBP10 is mainly involved in the response to stress conditions.